Liver Fibrosis Markers Improve Prediction of Outcome in Non‐Acetaminophen‐Associated Acute Liver Failure. Issue 11 (21st September 2018) - Ugamura, Aya; Chu, Po‐sung; Nakamoto, Nobuhiro; Taniki, Nobuhito; Ojiro, Keisuke; Hibi, Taizo; Shinoda, Masahiro; Obara, Hideaki; Masugi, Yohei; Yamaguchi, Akihiro; Shiba, Shunsuke; Morikawa, Rei; et al.
Abstract : A prognostic system for acute liver failure (ALF) with a higher predictive value is urgently needed. The role of extracellular matrix (ECM) remodeling in ALF has not been fully elucidated. We hypothesized that serologic fibrosis markers, which reflect ECM remodeling, are predictive of ALF outcome at first presentation. This observational study included 110 patients with acute liver dysfunction, of which 73 had non‐acetaminophen‐associated ALF (NAA‐ALF). We evaluated serum levels of hyaluronic acid, 7S domain of type IV collagen (4COL7S), and Wisteria floribunda agglutinin‐positive Mac‐2‐binding protein at first presentation to a tertiary center. Serologic fibrosis markers were significantly higher in NAA‐ALF compared with acute hepatitis. Elevated hyaluronic acid and 4COL7S levels at first presentation correlated significantly with worse clinical outcomes. 4COL7S, along with age, ammonia, and the Model for End‐Stage Liver Disease (MELD) score, was a significant prognostic factor in multivariate analysis; 4COL7S correlated significantly with coagulopathy, decreased hepatic synthetic functions, advanced hepatic encephalopathy, and liver atrophy and also predicted 180‐day transplant‐free survival. Cox regression models incorporating 4COL7S with the MELD system had profoundly improved predictive values that significantly surpassed the MELD system alone. Conclusion: Elevation of serologic fibrosis markers reflecting ECM remodeling in NAA‐ALF predicted a worse clinical outcome. Incorporation of 4COL7S at first presentation to a transplant center improves the specificity while retaining the sensitivity of the MELD system. External validation of a fibrosis marker as part of a clinical prediction tool in ALF warrants further investigation. Abstract : ECM remodeling is a universal histological phenomenon in non‐acetaminophen‐associated acute liver failure. Elevation of serological fibrosis markers that reflect ECM remodeling predicts a worse clinical outcome.